Comportamiento de los contribuyentes y su cumplimiento de obligaciones tributarias en el cantón Riobamba-Chimborazo, 2023 - Paredes Guamán, Darwin Alexis (2024)
ABSTRACT: The investigation sought to assess taxpayer behavior and compliance with tax obligations in the canton of Riobamba-Chimborazo, 2023, as it is a matter that could impact the Ecuadorian state for its development and tax payment of rubles. In addition, this research work aimed to determine the factors that influence the behavior of taxpayers and to identify the importance of tax collection. With the help of data collection techniques, 373 surveys were applied to registered taxpayers, active status, general and special regime, both obliged and non-obliged natural persons, with their establishment status open for the purpose of developing the objectives of this investigation. In addition, interviews were conducted with 7 professionals trained in the field of taxation, looking for criteria to validate the results obtained. Keywords: Tax behavior, tax obligations, taxpayer, tax collection.